IMPROVING STUDENTS SPEAKING SKILLS THROUGH DEBATE STRATEGY - Ina timbu, Maria Elisabeth; Bhoko, Maria Lusia; Keli, Eltrisna Wati (Ma Chung Press, 2023)
In this research, the authors utilize the debate technique to improve students' speaking ability. The main goals of this study were to describe the implementation of the debate technique in teaching speaking and to identify how much the students' speaking ability was improved after being taught by using the debate technique. This study is classroom action research conducted in two cycles. Data were collected using observation, tests, and interviews. Data from observations, tests, and interviews taken from each cycle were analyzed quantitatively and qualitatively. The application of the debate technique in teaching speaking in class XI IPS 1 the high school in Maumere was conducted in two cycles, namely cycle one and cycle two. The participants of this study were 16 students. The result of this study shows that the use of debate techniques can improve students' speaking skills. This is evidenced by the students' test scores which have increased in each cycle. In the first cycle, the student’s average score was 54.37% and in the second cycle, the student’s average score was 69.37%. It can be inferred that the debate technique can increase students' interest in speaking and can also upgrade the class to be more favorable